PENINGKATAN HASIL BELAJAR SISWA KOMPETENSI DASAR PERSAMAAN AKUNTANSI MELALUI PENDEKATAN PENDIDIKAN KARAKTER MENGGUNAKAN METODE GROUP INVESTIGATION - Widhiatmoko, Iman; Khafid, Muhammad (Dinamika Pendidikan, 2014)
The purpose of this study was to determine the use of character education approach through group investigation (GI) method in improving studentsâ€™ learning outcomes in learning accounting on the basic competence of accounting equation at MAN 1 Pekalongan. It was an experimental research with control group pre-test-post-test pattern. The data were collected by observation and tests. The data were analyzed by percentage descriptive and inferential statistical tests. The treatment can make students atÂ  experimental class are used to behave honestly. The result of hypothesis test showed that learning outcomes increased after the treatment in the experimental class. The average value of the post-test at experimental class was higher (75.08) than the control class (70.73).Â